LITERASI INFORMASI DALAM PERSPEKTIF LITERATUR DAN REALITAS LAPANGAN: STUDI KASUS MAHASISWA PRODI PERPUSTAKAAN DAN SAINS INFORMASI UNIVERSITAS MUHAMMADIYAH SINJAI - Nur Amalia; Syamsuddin (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2025)
This study aims to bridge the gap between academic discourse and practical implementation in the field of information literacy by employing two main approaches: bibliometric analysis of scientific publications and assessment of students' information literacy skills using the Big Six model. The research adopts a quantitative approach, utilizing two methods: bibliometric analysis and a descriptive survey through questionnaire distribution. The results indicate that the topic of information literacy has experienced significant growth over the past five years, with a particular focus on competency development, the role of higher education, and the application of the Big Six model in addressing digital era challenges. Concurrently, a survey of 29 students from the Library and Information Science Study Program at Universitas Muhammadiyah Sinjai revealed a high level of competence across all Big Six indicators, with the highest score recorded in the evaluation stage. The alignment between the bibliometric findings and field data suggests that the development of information literacy theory and practice is in sync, reflecting the effectiveness of integrating information literacy within the context of higher education.